Applying Constructivist Teaching Theory to Enhance Deep Learning in Contemporary Education Contexts - Valentine Flavian Ruhangisa; Ndeymariama Jammeh (EduGrows: Education and Learning Review, 2026)
The constructivist teaching theory has gained a new status in contemporary teaching practice, emphasizing the role of the learner in the process of meaning production as the result of his or her active involvement, reflection and dialogue. Theoretically, this approach has merit, but there is a lack of empirical studies regarding constructivist strategies to be applied in deep learning in teachers' practices. This is a qualitative phenomenological study which examines how 12 teachers in their secondary and higher education level classrooms implement constructivist theory in practice. The research methodology is semi-structured interviews, observations in the classroom, and document analysis to gain insight into teacher interpretations, teaching strategies and difficulties in implementing this research. It is found that the meaningfulness constructivist implementation needs inquiry-based learning, collaborative problem solving, scaffolding, and reflective learning. However, structural problems such as large classes, curriculum overload and assessment issues still pose a serious problem for authentic adoption. The findings of this study present empirical evidence on the constructivism-deep learning construct relationship and evidence-informed implications for teacher development, curriculum reform and educational policy.